Transient analysis of individual return temperatures in hydronic floor heating systems - Thorsteinsson , Simon; Lund Stærmose, Henrik; Bendtsen , Jan Dimon (CLIMA 2022 conference, 2022)
In this work, we investigate some potential benefits and opportunities gained from monitoring the return temperature of all the circuits in a hydronic floor heating (FH) system. It is for example possible to obtain information on the flow distribution in the FH system. Since flow sensors are relatively expensive, most currently installed FH systems do not provide any information on the flow entering the forward manifold, let alone flows in the individual circuits. This lack of information inhibits analysis of performance and prevents commissioning of more advanced control methods. The approach proposed here, based on temperature sensors mounted on the exterior of the pipes, provides a possible cheap alternative to measuring the flows directly. Further, we argue that this retrofitted solution can be applied to most already installed floor heating systems. The paper contains a description of the retrofit kit and a dynamic model, which is shown to be able to replicate the behaviour of measurements acquired from an actual FH system installed in a single family house, as well as a method for calculating the relative flows. The results show that flow related parameters such as circulation time are, under the right circumstances, directly observable in the data. Overall, we conclude that measuring the individual return temperatures provides valuable information when monitoring the health and performance of a floor heating system.